Effect of maternal nutritional status on the biochemical composition of human milk - Dias, Bina; Nakhawa, Devina P. (International Journal of Research in Medical Sciences, 2016)
Background: Infants normally thrive on their mother’s milk. The nutrients required to sustain such a rapid growth are all supplied by breast milk alone in the first 3-4 months of life, in all infants. The composition of human milk should therefore provide a clue to the physiological needs for energy and nutrients in infants. Methods: Sixty three milk samples of lactating mothers of full term babies were assessed for the levels of lactose, protein, triglyceride and cholesterol and were compared depending on their body mass index (BMI). Results: The result of the present study showed that lactose content of the milk ranged between 4.2 gm/dl to 9.7 gm/dl, with a mean of 6.47 gm/dl. Protein content ranged from 0.6 gm/dl to 7.1 gm/dl, with a mean of 2.4 gm/dl. Cholesterol had a wide range with a minimum of 4.8 gm/dl to a maximum of 99.4 mg/dl, with a mean of 32.3 mg/dl. Triglyceride had a mean value of 8.4 gm/dl, values ranging from 1.9 to 34.1 gm/dl. Conclusions: Breast milk composition is fairly constant and is not affected by maternal nutrition, or dietary intake.